IMPLEMENTASI PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL DI DESA PINANG JATUS KECAMATAN LONG KALI KABUPATEN PASER - Herida Erhan; Syahrumsyah Asri; Agus Santosa (Halu Oleo University, 2022)
The purpose of this study was to analyze the implementation of the remote indigenous community empowerment program (KAT) in the Liombe location, Pinang Jatus Village, Long Kali District, Paser Regency. The research was conducted in remote indigenous communities at the Liombe location, Pinang Jatus Village, Long Kali District, Paser Regency using a qualitative descriptive method and data collection procedures were carried out using in-depth interviews, observation and documentation techniques which were then analyzed using an interactive analysis model through the stages of data collection, data reduction, presentation of data and conclusions (Miles Huberman and Saldana 2014). The results showed that the implementation of the remote indigenous community policy at the Liombe Location, Pinang Jatus Village, Long Kali District, Paser Regency, initially in 2018 and 2019 went well because there were many programs and empowerment carried out by the government for the community and they really felt the impact given such as cultivating peanuts, corn and chilies as well as processing forest products, namely rattan. The impact on welfare, economic empowerment and social activity including in this case their political role is very much considered. As well as the inhibiting factors are the lack of and limited facilities for health, education, lack of lighting facilities, limited access to dirt roads and clean water